Efektivitas Media Pop Up dalam Peningkatan Kosa Kata pada Anak Tunagrahita Ringan Kelas IV di SLB Negeri Manekat Niki-Niki - Bahan, Estiresika; Wangge, Vinsensius; Selan, Ot Bil Wilson; Sene, Chamelya Vivi C. (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Education is a shared responsibility involving teachers, government, parents, and the community. One group of children who need special attention is children with mild intellectual disabilities, who have an intelligence level ranging from 50 to 70. Children with mild intellectual disabilities usually experience complex vocabulary problems that have an impact on mental development disorders or a lack of self-confidence. This study aims to improve vocabulary skills in children with mild intellectual disabilities using Pop Up Book media at SLB Negeri Manekat Niki-Niki, Amanuban Tengah District, South Central Timor Regency. The method used is classroom action research with a quantitative descriptive approach based on the Kurt Lewin model, which includes four stages: planning, action, observation, and reflection. The study subjects comprised three children: two boys and one girl. Data were collected through observation sheets for students. The results of the study in the first cycle showed an increase in the vocabulary skills of children with mild mental retardation who used Pop up. Book media. Thus, it can be concluded that the use of Pop Up. Book media is effective in improving vocabulary skills in children with mild mental retardation at SLB Negeri Manekat Niki-Niki.